2020
DOI: 10.1038/s41545-020-00082-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermocatalytic membrane distillation for clean water production

Abstract: Natural water bodies and treated wastewaters contain an increasing variety of organic micropollutants with a negative impact on ecosystems and human health. Herein, we propose an integrated process based on membrane distillation and advanced oxidation, in which thermal energy is simultaneously used to drive the permeation of pure water through a hydrophobic membrane and to activate the generation of reactive oxygen species by a thermocatalytic perovskite, namely Ce-doped strontium ferrate. At a feed temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…The experiments to investigate the thermocatalytic abatement during filtration were performed at a temperature of 50 °C, because our previous studies showed that CSF can catalyze fast degradation of BPA at this temperature [ 20 ]. The feed volume was 1.8 L, a cross flow of 1.6 ± 0.1 m s −1 was applied and the transmembrane pressure was 6 bar.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiments to investigate the thermocatalytic abatement during filtration were performed at a temperature of 50 °C, because our previous studies showed that CSF can catalyze fast degradation of BPA at this temperature [ 20 ]. The feed volume was 1.8 L, a cross flow of 1.6 ± 0.1 m s −1 was applied and the transmembrane pressure was 6 bar.…”
Section: Resultsmentioning
confidence: 99%
“…Such temperature-permeance dependence in ceramic NF membranes can be explained by considering the change in solvent viscosity and that permeation in micropores occurs by a combination of viscous flow and activated transport [ 24 ]. Hence, the increase of the feed temperature is beneficial for membrane permeance and for the thermocatalytic abatement at the same time [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the catalytic area, various oxide perovskites have shown thermocatalytic properties regarding the degradation of organic compounds by the formation of reactive oxygen species (oxygen-containing radicals) [5], which can be useful in the removal of micropollutants from wastewater in the future [6]. The catalytic site in perovskites is mainly located in the B-site (transition metal) due to their multiple oxidation states [7], covering, for example Ti [8,9], Fe [10,11], Co [12,13], and Mn [14]. However, doping and tuning the A-site can alter the band gap [15].…”
Section: Introductionmentioning
confidence: 99%
“…One of humanity's environmental issues is the growing worldwide pollution of the water supply caused by climate change, economization, overconsumption, and population growth 1 .…”
Section: Introductionmentioning
confidence: 99%